El Modelo Servqual Y Su Incidencia En El Nivel De Satisfacción De La Carrera De Economía De La Universidad Nacional De Chimborazo - María González Bautista; Eduardo Zurita Moreano; Mauricio Zurita Vaca (European Scientific Journal, ESJ, 2017)
This article is aimed at evaluating the level of satisfaction that both the internal and external clients of the Economics Career are experiencing. In the case of external clients through the application of the SERVQUAL model, considering that it is based on an analysis of the perception versus the expectation, it also evaluates the quality of service along five unique dimensions: reliability, responsiveness, security, empathy and tangible elements. The main result was that the ability to respond to the clients and provide willing and meaningful help to the users and provide fast service is the weakest parameter of the dimensions that the SERVQUAL Model values. In the case of internal clients, such as teachers, the level of satisfaction was assessed according to a specific methodology.